Determination of Seed Volume Based on Selected Seed Dimensions - Zdzisław Kaliniewicz; Dariusz Choszcz; Adam Lipiński (Applied Sciences, 2022)
The volume coefficient, which denotes a simple relationship between selected seed dimensions and seed volume, can be used to facilitate volume calculations in individual seeds, in particular in species with a complex seed shape. For this reason, seed thickness, width, and length were measured in nine species of forest trees and shrubs. The volume of seeds belonging to each plant species was determined by pycnometry, and the results were used to calculate 10 volume coefficients based on different combinations of basic seed dimensions. The calculated coefficients had different values, and they were lowest when volume was determined based on the cube of seed length and highest when volume was determined based on the cube of seed thickness. In a formula based on all three basic dimensions, the calculated volume coefficient ranged from 0.376 to 0.537, and Cornus macrophylla, Picea abies, and Cornus sanguinea seeds most closely resembled an ellipsoid. When seed volume was determined with the use of two basic dimensions, formulas based on the square of the smaller dimension produced somewhat smaller errors in individual seeds. In turn, seed thickness should be used in formulas that rely on a single dimension. Seed volume coefficients were most strongly correlated with the sphericity index, which indicates that this parameter can be used to estimate their values. The sphericity index was most strongly correlated with volume coefficients; the strongest correlations were observed for volume coefficients calculated based on the square of the seed length and seed width, and the cube of the seed length.